Pengaruh work life balance dan lingkungan kerja terhadap kinerja karyawan melalui komitmen Afektif sebagai variabel intervening - Marsyanda, Elza; Rozaq, Khoirur (Jurnal Ilmu Manajemen, 2024)
This study aims to analyse and examine the effect of work-life balance and work environment on employee performance through affective commitment in an electricity service provider company unit in Sidoarjo. This research is causality research with a quantitative approach. The sampling technique in this study used saturated samples with a total of 67 employees. The statistical analysis used in this research is Partial Least Square (PLS) with SmartPLS 3.2.9 software. The results of this study indicate that work-life balance has no effect on employee performance, work-life balance has a positive and significant effect on affective commitment, the work environment has a positive and significant effect on employee performance, the work environment has a positive and significant effect on affective commitment, affective commitment can mediate the effect of work-life balance on employee performance, affective commitment can mediate the effect of work environment on employee performance, and affective commitment has a positive and significant effect on employee performance.